F1 Holstein x Zebu Cows in late pregnancy show physiological adaptation when raised in semiarid environment - Diniz, Thamara Amaral; Carvalho, Cinara da Cunha Siqueira; Ferreira, Heberth Christian; Castro, Anna Luísa de Oliveira; Pereira, Kátia Cristiane Borges; Gonçalves, Maria Cecília Magalhães; Soares, Thaís Emanuele; Menezes, Jordana Carvalho (Revista de Ciências Agroveterinárias, 2017)
This study aimed to verify the adaptability of F1 Holstein x Zebu cows in the late pregnancy third, raised in the semiarid region of Minas Gerais, by means of physiological responses. A total of ten cows were used, all in fourth pregnancy. To characterize the climatic environment, daily collections of air temperature, air relative humidity and wind speed were carried out to enable the calculation of the Globe Temperature and Humidity Index (GTHI) and Radiant Thermal Load (RTL). The physiological parameters analyzed were: respiratory frequency, rectal temperature and surface body temperature, at 10 am and 3 pm. The adaptability tests used were Heat Tolerance Index (HTI) and Heat Tolerance Coefficient (HTC). The climatic environment was out of thermal comfort in the afternoon. There were significant differences (P <0.05) for the values of the physiological parameters. However, these responses were within the comfort range recommended for crossbred animals. The adaptability tests confirmed that the animals show adaptation to the semiarid environment of Minas Gerais, showing differences (P <0.05) on HTC between 10 am (2.52) and 3 pm (2.64), and the HTI showed an average of 9.64, a value that is very close to the index 10. It is concluded that the F1 Holstein x Zebu cows in the late pregnancy third are adapted to the climate in the semiarid region of Minas Gerais, for not altering their physiological behavior in face of the adversities of the climatic environment.